Neither Jew nor Greek: A Contested Identity (Christianity in the Making, Volume 3) - Dunn, James D. G. (Wm. B. Eerdmans Publishing Co, 2016)
Preface -- Part Ten: A New Beginning -- 38. Christianity in the Making -- 38.1 Introduction -- 38.2 The Emergence of the Great Church -- 38.3 Christianity and Judaism -- 38.4 The Hellenization of Christianity -- 38.5 A Contested Identity -- 39. The Sources - First Century(the New Testament) -- 39.1 The Diversity and Character of the Source Material -- 39.2 The Canonical Gospels -- 39.3 The Rest of the New Testament -- 40. The Sources - Second Century -- 40.1 The Apostolic Fathers -- 40.2 The Apologists -- 40.3 Eusebius and the Heresiologists -- 40.4 The Other Gospels -- 40.5 Other Letters -- 40.6 The Other Acts -- 40.7 Other Apocalypses -- 40.8 Summary -- Part Eleven: Jesus Still Remembered -- 41. From gospel to Gospel -- 41.1 The gospel before the Gospel -- 41.2 The Gospel of Mark -- 41.3 The Gospels of Matthew and Luke -- 41.4 The Gospel of John -- 41.5 The Gospel -- 42. Retelling the Story of Jesus:Mark, Matthew and Luke -- 42.1 From Oral Tradition to Written Gospel -- 42.2 The Gospel according to Mark -- 42.3 The Gospel according to Matthew -- 42.4 The Gospel according to Luke - and Acts -- 42.5 Jesus Remembered Becomes the Gospel of Jesus Christ -- 43. Reshaping the Gospel of Jesus:John and Thomas -- 43.1 The Gospel according to John -- 43.2 The Gospel of Thomas -- 43.3 Comparing John and Thomas -- 43.4 Is Thomas a 'Gospel'? -- 43.5 Two Different Gospels,Two Different Hermeneutical Strategies -- 44. The Jesus Tradition in the Second Century -- 44.1 Introduction -- 44.2 The Oral Jesus Tradition into the Second Century -The Apostolic Fathers -- 44.3 The Oral Jesus Tradition into the Second Century -The Apologists -- 44.4 Other Streams of Jesus Tradition -- 44.5 Gnostic Gospels 1 - The Issue of Early Source Material -- 44.6 Gnostic Gospels 2 -- 44.7 Narrative Gospels -- 44.8 The Recognition of the Four (Canonical) Gospels -- 44.9 Conclusions